SAT0053 The incident immunological status predicts drug-free disease flare in rheumatoid arthritis patients achieving stringent clinical and ultrasonographic control of the peripheral inflammatory process. (15th June 2017) - Manzo, A; Bugatti, S; Benaglio, F; Vitolo, B; Sakellariou, G; Caporali, R; Montecucco, C
Abstract : Background: The development of predictive tools to evaluate health risks and design personalized health plans in patients with rheumatoid arthritis (RA) achieving remission still represents a major unmet need. In this perspective, the relative weight of clinical, ultrasound and immunological assessment of disease characteristics for predicting recurrence of the inflammatory process under drug-free conditions remains unclear. Objectives: To investigate the predictive value of baseline clinical remission stringency, synovial power Doppler (PD) ultrasound indices and the incident autoimmune status, as predictors of flare under drug-free conditions after a DAS28-driven treatment strategy with methotrexate (MTX) in early RA. Methods: 85 RA patients achieving stable remission and candidate to MTX withdrawal were recruited according to the following criteria: 1) introduction of MTX within 12 months from symptoms' onset, 2) at least 24 months of MTX treatment with a DAS28-driven protocol targeting low disease activity (LDA), 3) DAS28<2.6 for ≥6 months in the absence of corticosteroids. Following treatment suspension, patients were monitored at three months' intervals across 24 months through clinical, ultrasound (hands-feet-axillary lymph nodes), radiographic and immunologic screenings (ACPA-RF status, CXCL13 circulating levels [1–2] and FACS analysis for quantification of Ki67+/regulatory T-B cell subsets). Treatment was re-introduced in case of DAS28≥3.2 or stable LDA. Results: At baseline, 84% of the patients were in remission according to the SDAI (<3, 3) with 44% of the cases showing SDAI remission and absence of PD signal in hands and feet (SDAI<3, 3 and PD=0). Despite stringent remission, 48% of the patients showed an episode of flare during follow-up with a peak incidence between 6 and 9 months after drug withdrawal. With the exception of a mild protective role of SDAI remission, none of the investigated clinical and ultrasound parameters (alone or in combination) showed a significant impact on clinical evolution across 24 months. ACPA IgG levels showed instead a strong, inflammation-independent predictive value for disease recurrence, an observation that was confirmed in the overall cohort (HR: 3.39 [1.7–6.64], p=0.0006, Cox regression) and, invariably, across progressive clinical and/or ultrasound remission thresholds (SDAI remission, SDAI remission-PD=0). Sub-analyses focused on short-term events (0–6 months after DMARDs withdrawal), identified the systemic level of CXCL13 at baseline as the strongest predictor of early disease recurrence in ACPA IgG positive individuals. Conclusions: The systemic immuno-type of patients in remission is the major determinant of drug-free disease recurrence, over and above drug-induced achievement of stringent clinical and ultrasonographic control of the peripheral inflammatory process. References: Meeuwisse CM et al. Identification of CXCL13 as a marker for rheumatoid arthritis outcome using an in silico model of the rheumatic joint. Arthritis Rheum 2011; 63: 1265–73. Havenar-Daughton C et al. CXCL13 is a plasma biomarker of germinal center activity. Proc Natl Acad Sci U S A 2016; 113: 2702–7. Disclosure of Interest: None declared